Error analysis of Students’ Recount Writing Text - Izla Wardany; Isna Humaera; Suhartini Syukri (AL LUGHAWIYAAT, 2021)
In this research, the researcher intended to find the significant error that occur in class X MIPA 1 SMAN 11 Kendari. By this research, the aim was to describe the main problem, the most common error which students made in their recount text writing at X MIPA 1 SMA Negeri 11 Kendari. Data is collected using Students writing draft. Students were asked to write a recount text at least 100 words in 45 minutes. The results of data analysis revealed that omission of auxiliary was the common error done by students X MIPA 1 SMA Negeri 11 Kendari. In students’ writing there are several errors that researcher have found that namely; omission of articles, omission of preposition, omission of apostrophe, omission of auxiliary, omission of countable and uncountable nouns. Based on the results, analysis students’ error is giving many the descriptions of students’ writing ability.